The Latent Diffusion Network among National Parliaments in the Early Warning System of the European Union. (19th January 2021) - Malang, Thomas; Leifeld, Philip
Abstract: Since the Treaty of Lisbon, national parliamentary chambers in the European Union can issue reasoned opinions on legislative proposals by the European Commission. These individual reasoned opinions lead to a review if at least one third of all chambers raise such concerns. Hence, coordination among parliaments is key. Using advances in inferential network analysis, this article infers the underlying diffusion pathways among national parliaments through which chambers are related to each other in their decisions to raise subsidiarity concerns. The emerging diffusion network is characterised by a compartmentalization into communities of European Union budget net contributor and net recipient countries. This descriptive finding has implications for the institutional effectiveness and aspired democratic legitimacy of the Early Warning System. A multivariate statistical network analysis confirms that diffusion occurs among net recipient countries and that weak institutions follow the lead of strong institutions in the Early Warning System.